2008
DOI: 10.1038/hdy.2008.61
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Oryza rufipogon Griff. in China

Abstract: Oryza rufipogon Griff. (common wild rice; CWR) is the ancestor of Asian cultivated rice (Oryza sativa L.). Investigation of the genetic structure and diversity of CWR in China will provide information about the origin of cultivated rice and the grain quality and yield. In this study, we used 36 simple sequence repeat (SSR) markers to assay 889 accessions, which were highly representative of whole germplasm in China. The analysis revealed a hierarchical genetic structure within CWR. First, CWR has diverged into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…; Wang et al . ). SNPs and indels have also been used in the rice genetic diversity researches recently (Yamanaka et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Wang et al . ). SNPs and indels have also been used in the rice genetic diversity researches recently (Yamanaka et al .…”
Section: Discussionmentioning
confidence: 97%
“…sativa and O . rufipogon has been investigated based on molecular markers, SNPs and indels [33], [34], [35], [36], [37]. These researches had suggested that there was a bottleneck in the domestication of O .…”
Section: Discussionmentioning
confidence: 99%
“…However, the fragmented nature of wetlands in this area has resulted in the hydrological disconnectivity between ponds or marshes and the arteries of rivers, which could have hindered the dispersal via seeds or propagules of the plant. Although episodic floods can result in temporary hydrological connectivity and facilitate the gene exchange, as suggested in O. rufipogon populations (Wang et al, 2008), high values of F ST and D est among pairs of populations along the same river indicate that episodic floods were not an effective path of dispersal for Z. latifolia.…”
Section: Roles Of Rivers Mountains and Fragmentationmentioning
confidence: 96%